2011
DOI: 10.1093/cid/cir075
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Tuberculosis Treatment Regimens in Chinese Tuberculosis Hospitals

Abstract: This investigation of tuberculosis (TB) treatment regimens in 6 TB hospitals in China showed that only 18% of patients with new cases and 9% of patients with retreatment cases were prescribed standard TB treatment regimens. Adherence to treatment guidelines needs to be improved in TB hospitals to control multidrug-resistant TB in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…Unfortunately, inappropriate treatment of MDR-TB has been a serious problem in China, particularly in hospitals. 24,28 Therefore, treating patients with MDR tuberculosis on the basis of results of drug susceptibility testing should become a mandatory policy.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, inappropriate treatment of MDR-TB has been a serious problem in China, particularly in hospitals. 24,28 Therefore, treating patients with MDR tuberculosis on the basis of results of drug susceptibility testing should become a mandatory policy.…”
Section: Discussionmentioning
confidence: 99%
“…However, impacts of the health reform on generally low availability [38], total number of prescriptions [39, 40] or less-than-appropriate use [41] was not clear.…”
Section: Resultsmentioning
confidence: 99%
“…The TB component of the infectious and endemic disease control (IEDC-TB) project in the People’ Republic of China indicated that new smear-positive cases should be treated with 2HRZS/4HR regimen [11, 19]. Patients treated in non-CTDs had a lower possibility to obtain the standardized chemotherapy regimens than those treated in CTD and a previous study by Chinese National Center for TB Control and Prevention showed similar results that only a small proportion of TB cases in hospitals (non- CTDs) were treated with appropriate NTP/WHO treatment regimens [20]. As improper therapeutic strategy could result in an extra burden not only to the patients but also to the community by increasing chances of drug resistance development, non-CTDs were proved to be less efficient in TB control in this respect.…”
Section: Discussionmentioning
confidence: 97%